Grading Severity of Productive Cough Based on Symptoms and Airflow Obstruction. (4th March 2018) - Vazquez Guillamet, Rodrigo; Petersen, Hans; Meek, Paula; Sood, Akshay; Tesfaigzi, Yohannes
ABSTRACT: The binary approach to the diagnosis of Chronic Bronchitis (CB) is a major barrier to the study of the disease. We investigated whether severity of productive cough can be graded using symptoms and presence of fixed airflow obstruction (FAO), and whether the severity correlates with health status, exposures injurious to the lung, biomarkers of inflammation, and measures of airway wall thickening. Findings from a cross-sectional sample of 1, 422 participants from the Lovelace Smokers Cohort (LSC) were validated in 4, 488 participants from the COPDGene cohort (COPDGene). Health status was based on the St. George's Respiratory Questionnaire, and Medical Outcomes Study 36-Item Short Form Health Survey. Circulating CC16 levels were quantified by ELISA (LSC), and airway wall thickening was measured using computed tomography (COPDGene). FAO was defined as postbronchodilator FEV1 /FVC <0.7. The presence and duration of productive cough and presence of FAO or wheeze were graded into Healthy Smokers, Productive Cough (PC), Chronic PC, PC with Signs of Airflow Obstruction, and Chronic PC with Signs of Airflow Obstruction. In both cohorts, higher grade of severity correlated with lower health status, greater frequency of injurious exposures, greater airway wall thickening, and lower circulating CC16 levels. Further, longitudinal follow-up suggested that disease resolution can occur at every grade of severity but is more common in groups of lower severity and least common once airway remodeling develops. Therefore, severity of productive cough can be graded based on symptoms and FAO and early intervention may benefit patients by changing the natural history of disease.